Penyelesaian Kredit Macet Melalui Jalur Non Litigasi Pada PT. Astra Credit Companies Pekanbaru Berdasarkan Undang-Undang Nomor 30 Tahun 1999 Tentang Arbitrase Dan Alternatif Penyelesaian Sengketa - Anwar Saleh Hasibuan; Dian Lolyna Elisabet Sagala; Nurainun (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
In meeting primary and secondary needs, not all people have sufficient economic capacity to buy and fulfill their needs. The birth of financing institutions such as business entities outside banks or non-bank financial institutions that provide loan facilities for costs or goods and services according to the abilities and needs of the community. However, often on the way there is an inability of consumers to pay which causes bad credit. One of them occurs at PT Astra Credit Companies Pekanbaru City which still finds problems in credit which results in bad credit. This research is classified into the type of empirical legal research, namely research obtained from facts or realities that exist in the life of a society. The nature of the research is descriptive qualitative with interview methods with competent respondents to be able to provide information related to research. The conclusion in this paper is that the credit process at PT Astra Credit Companies Pekanbaru does not always run smoothly. Not all debtors have good personalities and are responsible for their obligations. From this, bad credit arises and will be continued with various ways of settlement. One of the settlements is through non-litigation which is reviewed based on Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. Dispute resolution outside the court or through non-litigation is an effective resolution carried out without any process in court and outlines part of the settlement process through negotiation and mediation.